2023
DOI: 10.1097/ta.0000000000003870
|View full text |Cite
|
Sign up to set email alerts
|

Institutional outcomes of blunt liver and splenic injury in the Arizona-Texas-Oklahoma-Memphis-Arkansas Consortium era

Abstract: Management decisions for children with blunt liver and splenic injuries may be based solely on hemodynamic status and not injury severity grade by imaging. Check out the outcomes from a single pediatric trauma center when the #ATOMAC guidelines are used #SoMe4PedSurg #PedSurg

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…ICU admission is now recommended only for patients with persistently abnormal vital signs indicating hemodynamic instability despite adequate fluid resuscitation, regardless of grade [ 13 ]. While recent studies have shown that high-grade SOI remains an independent risk factor for ICU admission, many patients with high-grade SOI also demonstrate hemodynamic instability that would result in ICU admission regardless based on the updated guidelines [ 59 , 60 ].…”
Section: Level Of Care and Inpatient Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…ICU admission is now recommended only for patients with persistently abnormal vital signs indicating hemodynamic instability despite adequate fluid resuscitation, regardless of grade [ 13 ]. While recent studies have shown that high-grade SOI remains an independent risk factor for ICU admission, many patients with high-grade SOI also demonstrate hemodynamic instability that would result in ICU admission regardless based on the updated guidelines [ 59 , 60 ].…”
Section: Level Of Care and Inpatient Managementmentioning
confidence: 99%
“…Over the years, it has become evident that this approach likely overutilizes hospital resources, and a 2014 study demonstrated that pediatric surgeons were already shortening LOS for BLSI despite the recommendations [ 2 ]. Since shifting to management based on hemodynamic status rather than injury grade, there have been significant reductions in LOS without increases in adverse events [ 28 , 59 , 127 ]. One study evaluating patients with BLSI managed at both ATCs and PTCs found that while hospital LOS has decreased at each of these centers over time, LOS remains higher than what would be expected based on current APSA guidelines and further reinforcement of guidelines within the national trauma network, and particularly at ATCs, may be necessary [ 77 ].…”
Section: Activity Restrictions and Hospital Dischargementioning
confidence: 99%